Characteristics of a dielectric barrier discharge in atmospheric air - Lai, C.K.; Chin, O.H.; Thong, Kwai Lin (2009)
Parallel plate dielectric barrier discharges consisting of two electrodes with glass (εr = 7.5) and alumina (εr = 9.0) as the dielectric barrier were constructed. The system is powered by a variable 20 kV high voltage supply which is capable of delivering unipolar voltage pulses at frequency of 0.1–2.5 kHz and sinusoidal voltages at 6.5 kHz and above. At atmospheric pressure, the discharges exhibit either diffuse or filamentary appearance depending on parameters which include the series capacitance established by the electrodes with the dielectric barrier and varying air gap, dielectric material, and frequency of the supply voltages. This DBD system is built for the study of bacterial sterilization.